Verbal Courtesy in Directive Speech Acts: A Pragmatic Analysis of Requests in Hierarchical Workplace Contexts with Asymmetric Communicative Relationships - Ahumada Moncada, Silvana Patricia (2025)
While directive speech acts are inherent to hierarchical communication, their impositive nature can create relational friction. This study addresses a gap in pragmatic research by analyzing the specific verbal politeness strategies used by managers to mitigate requests to subordinates within a Colombian corporate context. Drawing from a corpus collected via the Discourse Completion Test, the findings reveal that mitigating politeness is the predominant interactional strategy. Linguistic resources such as informal address (tuteo) function to build solidarity, while modalizers and the modesty plural diminish the perceived authority gap. The study concludes that these politeness strategies are not merely optional, but a fundamental mechanism for maintaining organizational harmony, holding direct implications for management practice and intercultural communication training.